Proton exchange membrane, proton exchange membrane fuel cell, method and application
By introducing amino acid modified cellulose nanocrystals into sulfonated polyether ether ketones to form hydrogen bond clusters or ion clusters, the proton conductivity and mechanical stability problems in existing proton exchange membrane fuel cells are solved, and efficient protons are achieved Combination of conduction and mechanical strength.
Patent Information
- Application Number
- CN202411406716.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-10
- Publication Date
- 2025-02-14
AI Technical Summary
In the existing proton exchange membrane fuel cells, the Nafion membrane has problems such as complex preparation process, high cost, and reduced high temperature performance. The sulfonation degree of sulfonated polymers will affect the proton conductivity and mechanical stability of the membrane. .
By introducing amino acid modified cellulose nanocrystals into sulfonated polyether ether ketones, multiple hydrogen bonding clusters or ion clusters are formed, the number of proton transfer channels is increased, and hydrogen bonding and static electricity between amino acids and sulfonated polymers is increased, and the hydrogen bonding and static electricity between amino acids and sulfonated polymers is increased. Interactions enhance the mechanical strength of the membrane.
While improving the proton conductivity, it ensures the mechanical strength and chemical stability of the membrane, reduces material costs, and has good application potential in technical fields such as fuel cells.
Smart Images

Figure CN119447391A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of proton exchange membranes, and in particular to a proton exchange membrane, a proton exchange membrane fuel cell, a method and an application thereof. Background Art
[0002] The description of the background technology in the present invention belongs to the related technology related to the present invention, which is only used to illustrate and facilitate the understanding of the invention content of the present invention, and should not be understood as the applicant explicitly believes or inferred that the applicant believes that it is the prior art of the present invention on the filing date of the first application.
[0003] Proton exchange membrane fuel cell (PEMFC) is a device that can directly convert chemical energy into electrical energy, with the advantages of being green, efficient, and having a long service life. Proton exchange membrane (PEM) is an important component of PEMFC. It only allows protons to pass through, while preventing direct electron conduction and gas permeation between the anode and cathode. It has the following main functions: i) acts as a barrier to the mixture of redox reactants; ii) allows protons to move from the anode to the cathode, ensuring high proton transport; iii) acts as an effective insulator for electrons, preventing them from passing through the membrane; iv) has good mechanical and chemical resistance; and v) has low manufacturing cost and high durability; the quality of its performance directly determines the performance of PEMFC.
[0004] Currently, Nafion membranes are more common in the market. However, perfluorosulfonic acid membranes represented by Nafion membranes have problems such as complex preparation process, high cost, and decreased high temperature performance. Proton conductivity is one of the most important parameters for measuring the performance of proton exchange membranes. Improving proton conductivity is an effective means to obtain high-performance proton exchange membrane fuel cells. In recent years, using the characteristics of nanofibers such as high specific surface area, large aspect ratio, and easy surface structure modification to construct proton transfer channels has become an important method to improve proton conductivity performance.
[0005] Sulfonated polyetheretherketone (SPEEK) has the advantages of strong processability, good stability and low cost, and is expected to become a substitute for Nafion. Although the proton conductivity is not as good as Nafion, the material cost is relatively low and it can be modified, so it has become the main direction of PEM research today. However, sulfonated polymers also have some disadvantages: when the degree of sulfonation is low, the proton conductivity of the membrane will decrease; when the degree of sulfonation is too high, the membrane will also swell excessively, affecting the dimensional stability of the membrane. Summary of the invention
[0006] The purpose of the embodiments of the present invention is to provide a proton exchange membrane, a proton exchange membrane fuel cell, a method and an application. The modified cellulose nanocrystals of the present invention contain a large number of hydrophilic groups, hydroxyl groups and amino groups, which can form multiple hydrogen bond clusters or ion clusters with -SO3H in the sulfonated polymer. The formation of hydrogen bond clusters will also provide more proton transfer channels, thereby improving the high efficiency of proton transfer; at the same time, the hydrogen bonds and electrostatic interactions between the amino acid basic groups and SPEEK can effectively ensure the mechanical strength of the membrane.
[0007] The purpose of the embodiment of the present invention is achieved through the following technical solutions:
[0008] A method for preparing a proton exchange membrane comprises the following steps:
[0009] The sulfonated polyetheretherketone solution is prepared by dissolving the sulfonated polyetheretherketone in dimethyl sulfoxide, and the amino acid modified cellulose nanocrystal powder is added to obtain a uniform and stable solution, and the casting solution is obtained after filtering; the casting solution is used in an amount of 3-5 mL / cm 2 The casting liquid is dripped onto the membrane laying plate and maintained at 80° C. to 90° C. for 24 to 26 hours. The obtained composite membrane is the sulfonated polyetheretherketone / modified cellulose composite proton exchange membrane.
[0010] Furthermore, the sulfonated polyetheretherketone is prepared by the following steps:
[0011] The polyetheretherketone particles are dried under vacuum conditions at 100°C to 120°C to remove moisture, and the dried polyetheretherketone particles are added to concentrated sulfuric acid at a mass volume ratio of 1g:10mL, and stirred at 25°C to 30°C for reaction for 3 to 5 hours, and then the temperature is raised to 50°C to 80°C within 30 to 50 minutes, and stirring is continued for 5-8 hours. The reaction product is slowly poured into deionized water containing ice cubes to obtain white filamentous sulfonated polyetheretherketone; the product is washed to neutrality; and dried to obtain yellow sulfonated polyetheretherketone with a sulfonation degree of 50 to 60%.
[0012] Furthermore, the cellulose nanocrystal powder is prepared by the following steps: adding microcrystalline cellulose to 64% to 67% sulfuric acid at a mass volume ratio of 1 g / 17.5 mL to 1 g / 20 mL; stirring the suspension and heating it to 45°C to 50°C for 3.5 to 4.5 hours. After the reaction is completed, the solution is poured into water to terminate the reaction and obtain a CNC suspension; and the CNC is separated from the suspension by centrifugal washing.
[0013] Furthermore, separating CNC from the suspension by centrifugal washing specifically includes the following steps: centrifuging the suspension at a speed of 11,000 to 13,000 rp / min for 30 to 45 minutes, washing and mixing to obtain a mixed solution; placing the mixed solution in a dialysis bag with a molecular weight cutoff value of 8,000 to 14,000, and dialyzing until the pH value of the water reaches 6.5 to 7.0; vacuum freeze-drying the dialyzed sample to obtain CNC powder.
[0014] Furthermore, amino acid modified cellulose nanocrystalline powder is prepared by the following steps: CNC powder, NN dimethylformamide, L-serine, NN-diisopropylcarbodiimide, and 4-lutidine are added to a beaker at a molar ratio of 1 g: 10 mL: 6 mmol: 2.4 mmol: 1.8 mmol, shaken at room temperature, and then treated with 1-2% trifluoroacetic acid in anhydrous acetonitrile solution, DMF, 1-2% trifluoroacetic acid aqueous solution, anhydrous ethanol, an ethanol aqueous solution with a volume ratio of 1:3, and anhydrous ethanol, and finally vacuum dried to obtain amino acid modified CNC, named: CW-Fmoc-ser; the CW-Fmoc-ser obtained above is placed in a mixed solution to remove the protecting group, the mixed solution includes piperidine and NN dimethylformamide, and finally freeze-dried to obtain AAs modified CWs, named: CW-ser.
[0015] In another aspect, a proton exchange membrane is provided. The proton exchange membrane is prepared by the above-mentioned preparation method.
[0016] In another aspect, a use of a proton exchange membrane is to apply the above-mentioned proton exchange membrane to a proton exchange fuel cell.
[0017] In another aspect, a proton exchange membrane fuel cell is provided, wherein the proton exchange membrane of the proton exchange membrane fuel cell is the above-mentioned proton exchange membrane.
[0018] The embodiments of the present invention have the following beneficial effects:
[0019] Amino acids exist in the form of zwitterions, which can act as donors and acceptors of proton transfer, providing more proton transfer sites. When amino acids are properly arranged, they promote the protons to be carried along the arrangement of zwitterions. Based on this, nanofibers are introduced, and amino acids are immobilized on the surface of nanofibers to form amino acid clusters as carriers of proton transfer, and embedded in sulfonated polymers to prepare nanofiber hybrid membranes, to construct continuous long-range proton transfer channels, thereby improving the proton conduction performance of nanofiber hybrid membranes.
[0020] Compared with the SPEEK composite membrane prepared by the prior art, the modified cellulose nanocrystals in the present invention contain a large number of hydrophilic groups, hydroxyl and amino groups, which can form multiple hydrogen bond clusters or ion clusters with -SO3H in the sulfonated polymer. The formation of hydrogen bond clusters will also provide more proton transfer channels, thereby improving the efficiency of proton transfer; at the same time, the hydrogen bonds and electrostatic interactions between the amino acid basic groups and SPEEK can effectively ensure the mechanical strength of the membrane. The prepared sulfonated polyetheretherketone / modified cellulose nanofiber proton exchange membrane shows great application potential in fuel cells, including but not limited to the technical fields of water electrolysis to produce hydrogen, fuel cells, etc.
[0021] The design idea of the sulfonated polyetheretherketone / modified cellulose nanofiber proton exchange membrane proposed in the present invention is to use SPEEK as the main body, add modified cellulose nanocrystals and then prepare it by casting method. Its preparation process mainly includes: preparation of SPEEK, preparation of cellulose nanocrystal powder, preparation of amino acid modified cellulose nanocrystal powder and preparation of SPEEK / modified cellulose nanofiber proton exchange membrane. Sulfonated polyetheretherketone / modified cellulose nanofiber proton exchange membrane is prepared by casting method. The proton exchange membrane has excellent proton conductivity. By changing the content of modified CNC powder, the hydrogen bond interaction in the membrane can be regulated. The introduction of acid-base pairs in SPEEK can effectively reduce the proton transfer energy barrier and strengthen proton conduction. At the same time, the rich hydrogen bond interaction gives the membrane a certain mechanical strength and toughness. The preparation method of the present invention is mild, controllable, simple and efficient. The prepared membrane has both high proton conductivity and certain mechanical strength, and has good chemical and long-term operating stability, which is conducive to its wide application in hydrogen energy conversion technology. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 This is a SEM image of the finished membrane prepared in Example 3 of the present invention. The proton exchange membrane was broken and the cross-section of the proton exchange membrane was observed using a scanning electron microscope. The observation results are shown in the figure. It can be seen from the figure that the interior of the membrane is fully filled and cellulose nanoparticles are distributed in the matrix.
[0023] Figure 2 This is the power density diagram of Example 3 of the present invention. It can be seen from the figure that the maximum power density of Example 3 is 105mV / m 2 , the open circuit voltage is 568mV. DETAILED DESCRIPTION
[0024] The present application is further described below in conjunction with embodiments.
[0025] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, in the following description, different "one embodiment" or "embodiment" does not necessarily refer to the same embodiment. Different embodiments can be replaced or combined, and for ordinary technicians in this field, other implementation methods can be obtained based on these embodiments without creative work.
[0026] A method for preparing a proton exchange membrane, characterized in that it comprises the following steps:
[0027] The sulfonated polyetheretherketone solution is prepared by dissolving the sulfonated polyetheretherketone in dimethyl sulfoxide, and the amino acid modified cellulose nanocrystal powder is added to obtain a uniform and stable solution, and the casting solution is obtained after filtering; the casting solution is used in an amount of 3-5 mL / cm 2 The casting liquid is dripped onto the membrane laying plate and maintained at 80-90° C. for 24-26 hours. The obtained composite membrane is the sulfonated polyetheretherketone / modified cellulose composite proton exchange membrane.
[0028] Furthermore, the sulfonated polyetheretherketone is prepared by the following steps:
[0029] The polyetheretherketone particles are dried under vacuum conditions at 100-120°C to remove moisture, and the dried polyetheretherketone particles are added to concentrated sulfuric acid at a mass volume ratio of 1g:10mL, and stirred in a constant temperature water bath at 25-30°C for 3-5 hours, and then the temperature is raised to 50-80°C within 30-45 minutes, and stirring is continued for 5-8 hours, and the reaction product is slowly poured into deionized water containing ice cubes to obtain white filamentous sulfonated polyetheretherketone; washed to neutral; dried to obtain yellow sulfonated polyetheretherketone with a sulfonation degree of 50-60%;
[0030] In some embodiments, the polyetheretherketone particles are dried at 100° C. under vacuum conditions for 24 hours to remove moisture, and the dried polyetheretherketone particles are added to concentrated sulfuric acid one by one according to a mass volume ratio of 10 g / 100 mL, reacted in a constant temperature water bath, mechanically stirred at 25° C. for 3 hours, then heated to 50° C. within 30 minutes, and mechanically stirred for 5-8 hours, and the reaction product is slowly poured into deionized water containing ice to obtain white filamentous sulfonated polyetheretherketone; the sulfonated polyetheretherketone is washed with a large amount of deionized water to neutrality; and dried to obtain yellow sulfonated polyetheretherketone with a sulfonation degree of 50-60%;
[0031] Furthermore, cellulose nanocrystal powder is prepared by the following steps: adding microcrystalline cellulose to sulfuric acid with a mass fraction of 64-67% according to a mass volume ratio of 1g:17.5mL; stirring the suspension and heating it to 45-50°C for 3.5-4.5 hours. After the reaction is completed, the solution is poured into water to terminate the reaction and obtain a CNC suspension; and the CNC is separated from the suspension by centrifugal washing.
[0032] In some embodiments, preparation of cellulose nanocrystal (CNC) powder: adding microcrystalline cellulose to 64% sulfuric acid at a mass volume ratio of 1g / 17.5mL; stirring the suspension and heating it to 45°C for 3.5 hours. After the reaction is completed, the solution is poured into 5 times deionized water to terminate the reaction to obtain a CNC suspension; the NCC is separated from the suspension by centrifugal washing. The suspension is centrifuged at a speed of 11000rp / min for 30 minutes and washed 3 times; the mixed solution is placed in a dialysis bag with a molecular weight cutoff of 8000-14000 and dialyzed for 5-7 days until the pH value of the water reaches 6.5 to 7.0; the dialyzed sample is placed in a small beaker, frozen at -18°C in a freezer storage box for 48 hours, and then vacuum freeze-dried to obtain CNC powder.
[0033] Furthermore, separating CNC from the suspension by centrifugal washing specifically includes the following steps: centrifuging the suspension at a speed of 11,000 to 13,000 rp / min for 30 to 45 minutes, washing and mixing to obtain a mixed solution; placing the mixed solution in a dialysis bag with a molecular weight cutoff value of 8,000 to 14,000, and dialyzing until the pH value of the water reaches 6.5 to 7.0; vacuum freeze-drying the dialyzed sample to obtain CNC powder.
[0034] Furthermore, amino acid modified cellulose nanocrystalline powder is prepared by the following steps: CNC powder, DMF (NN dimethylformamide), L-serine), DIC (NN-diisocyanate carbodiimide), DMAP (0.219g 4-lutidine) are added to a beaker at a molar ratio of 1g:10mL:6mmol:2.4mmol:1.8mmol, shaken at room temperature, and then treated with 1-2% trifluoroacetic acid in anhydrous acetonitrile solution, DMF, 1-2% trifluoroacetic acid aqueous solution, anhydrous ethanol, ethanol aqueous solution with a volume ratio of 1:3, anhydrous ethanol, and finally vacuum dried to obtain amino acid modified CNC, named: CW-Fmoc-ser; the CW-Fmoc-ser obtained above is placed in a mixed solution to remove the protecting group, the mixed solution includes piperidine and NN dimethylformamide, and finally freeze-dried to obtain AAs modified CWs, named: CW-ser.
[0035] In some embodiments, amino acid modified cellulose nanocrystal powder is prepared: the CNC powder prepared in step 2, 10 mL DMF (NN dimethylformamide), 6 mmol (0.63 g) FAAs (L-serine L-Serine), 2.4 mmol (0.2445 ml) DIC (NN-diisocyanate carbodiimide), and 1.8 mmol DMAP (0.219 g 4-lutidine) are added to a beaker, shaken at room temperature for 3 hours, and then respectively treated with 1% trifluoroacetic acid in anhydrous acetonitrile solution, DMF, 1% trifluoroacetic acid aqueous solution, anhydrous ethanol, an ethanol aqueous solution with a volume ratio of 1:3, and anhydrous ethanol, and finally vacuum dried to obtain amino acid-modified CNC, named: CW-Fmoc-ser; the CW-Fmoc-ser sample obtained above is placed in a mixed solution (Pieridine and DMF (NN dimethylformamide)) to remove the protecting group, and finally freeze-dried to obtain AAs-modified CWs, named: CW-ser.
[0036] In another aspect, a proton exchange membrane is provided. The proton exchange membrane is prepared by the above-mentioned preparation method.
[0037] In another aspect, a use of a proton exchange membrane is to apply the above-mentioned proton exchange membrane to a proton exchange fuel cell.
[0038] In another aspect, a proton exchange membrane fuel cell is provided, wherein the proton exchange membrane of the proton exchange membrane fuel cell is the above-mentioned proton exchange membrane.
[0039] Example 1
[0040] The steps of preparing sulfonated polyetheretherketone / modified cellulose nanofiber proton exchange membrane are as follows:
[0041] Step 1, preparation of SPEEK: commercially available PEEK particles are dried under vacuum conditions at 100°C for 24 hours to remove moisture, etc. 12g of dried PEEK is added to 100mL of concentrated sulfuric acid, reacted in a constant temperature water bath, mechanically stirred at 25°C for 3 hours, then heated to 50°C within 30 minutes at the same heating rate, and after continuous mechanical stirring for 8 hours, the reaction product is slowly poured into mechanically stirred deionized water containing ice cubes to obtain white filamentous SPEEK. SPEEK is washed with a large amount of deionized water to pH = 7.0, and dried to obtain yellow SPEEK with a sulfonation degree of 60%.
[0042] Step 2, preparation of cellulose nanocrystal (CNC) powder: add microcrystalline cellulose to 64% sulfuric acid at a mass volume ratio of 1g / 17.5mL; stir the suspension continuously and heat it to 45°C for 3.5 hours. After the reaction is completed, pour the solution into 5 times deionized water to terminate the reaction and obtain a CNC suspension; separate NCC from the suspension by centrifugal washing. The suspension is centrifuged at a speed of 11000rp / min for 30 minutes and washed 3 times; the mixed solution is placed in a dialysis bag with a molecular weight cutoff value of 8000-14000 and dialyzed for 5-7 days until the pH value of the water reaches 6.5-7.0; the dialyzed sample is placed in a small beaker, frozen at -18°C in a freezer storage box for 48 hours, and then vacuum freeze-dried to obtain CNC powder.
[0043] Step 3, preparation of amino acid modified cellulose nanocrystal powder: 1g of CNC powder prepared in step 2, 10mL DMF (NN dimethylformamide), 6mmol (0.63g) FAAs (L-serine L-Serine), 2.4mmol (0.2445ml) DIC (NN-diisocyanate carbodiimide), 1.8mmol DMAP (0.219g 4-lutidine) were added to a beaker, shaken at room temperature for 3h, and then treated with 1% trifluoroacetic acid in anhydrous acetonitrile solution, DMF, 1% trifluoroacetic acid aqueous solution, anhydrous ethanol, ethanol aqueous solution with a volume ratio of 1:3, anhydrous ethanol, and finally vacuum dried to obtain amino acid modified CNC; the CNC sample obtained above was placed in a mixed solution (Pieridine and DMF (NN dimethylformamide)) to remove the protecting group, and finally freeze-dried to obtain AAs modified CWs powder.
[0044] Step 4: dissolve 1 g of the sulfonated polyetheretherketone prepared in step 1 in 10 ml of DMSO to prepare a 10% SPEEK solution, stir at room temperature for 6 hours, then add 30 mg of the CWs powder prepared in step 3 while stirring, ultrasonically vibrate for 2 hours, and stir at room temperature for 6 hours to obtain a uniform and stable solution, which is filtered with a filter cloth to obtain a casting liquid; use a casting method to drop the casting liquid onto a 5×5 cm film-laying plate, and maintain it at 80°C for 24 hours to obtain a sulfonated polyetheretherketone / modified cellulose composite membrane 1.
[0045] Example 2
[0046] The sulfonated polyetheretherketone / modified cellulose composite membrane was prepared. The preparation process was basically the same as that in Example 1, except that in step 4, the amount of CWs powder used was determined according to a mass ratio of 0.06:1 with SPEEK, and the final SPEEK / modified cellulose composite membrane 2 was obtained.
[0047] Example 3
[0048] The sulfonated polyetheretherketone / modified cellulose composite membrane was prepared in a process that was basically the same as that in Example 1, except that in step 4, the amount of CWs powder used was determined according to a mass ratio of 0.09:1 with SPEEK, and the final SPEEK / modified cellulose composite membrane 3 was obtained.
[0049] The proton conductivity of this embodiment is compared with that of a commercially available membrane (Nafion 117) as shown in Table 1. It can be seen that the finished membrane prepared by the present invention has better performance.
[0050] Example 4
[0051] The sulfonated polyetheretherketone / modified cellulose composite membrane was prepared in the same process as in Example 1, except that in step 4, the amount of CWs powder used was determined according to a mass ratio of 0.12:1 with SPEEK, and the final SPEEK / modified cellulose composite membrane 3 was obtained.
[0052] Comparative Example 1
[0053] Preparation of pure SPEEK membrane, the steps include:
[0054] Step 1, SPEEK preparation: the same as step 1 of Example 1.
[0055] Step 2, preparation of pure SPEEK membrane: DMSO was added to 300 mg SPEEK to prepare 5 mL of mixed solution, stirred at room temperature for 24 h, ultrasonicated for 15 min before and after stirring, and filtered with filter cloth to obtain casting solution. The membrane-building solution was dropped onto a 5 cm × 5 cm membrane-laying plate by casting method, and maintained at 80°C for 24 h to obtain pure SPEEK membrane.
[0056] The sulfonated polyetheretherketone / modified cellulose composite membranes and pure SPEEK membranes obtained in Examples 1-4 and Comparative Examples were subjected to performance tests, and the obtained data are listed in Table 1;
[0057] Proton conductivity: The resistance of the sample membrane was measured by CHI600E electrochemical workstation and its two electrodes (detection temperature 100°C, humidity, and then the proton conductivity was calculated by formula 1:
[0058]
[0059] Where σ is the proton conductivity of the membrane, S and d are the area and thickness of the measured membrane, respectively, and R is the resistance of the membrane.
[0060] Water absorption: Water absorption was tested by immersion in pure water at room temperature.
[0061]
[0062] Where: W wet is the mass of the film in wet state, W dry is the mass of the film in dry state.
[0063] Table 1
[0064]
[0065] By comparing Examples 1 to 4 and the comparative example, it can be concluded that when the filling amount of CNC powder increases, the ordered pores in the zwitterionic CNC-SER provide a proton transfer path; the abundant acidic groups -SO3H in the pores provide proton transfer sites; the abundant amino groups on the skeleton form a donor-acceptor group structure with -SO3H, which reduces the proton transfer energy barrier and strengthens conduction. It can be specifically concluded from Table 1 that when the CNC / Ser content is 9%, the obtained membrane ion proton conductivity is optimal, and the proton conductivity is higher than that of comparative example 1. This is because at this time, the amino groups in SER combine with the sulfonic acid groups in SPEEK to form an acid-base pair, which promotes proton jumping. At the same time, the large number of hydroxyl groups contained in CNC can adsorb more water molecules; when the mass fraction of CNC / Ser increases, SER will form clusters on the surface of the SPEEK membrane, resulting in the generation of large pores, thereby causing the ion selectivity to deteriorate.
[0066] The sulfonated polyetheretherketone / modified cellulose composite membranes and pure SPEEK membranes obtained in Examples 1-4 and Comparative Examples were placed in a fuel cell to test the power generation performance. The voltage value was recorded using a digital multimeter. When the voltage dropped to 0, the total Fe ion removal rate of the anode solution was measured. The obtained data are listed in Table 2.
[0067] In the experiment, Examples 1-4 and Comparative Examples 1 and 2 were placed in a fuel cell, and an acid mine drainage removal experiment was conducted at room temperature to measure the maximum power density generated. At the same time, when the voltage dropped to 0, the experimental data of the Fe ion removal rate of the anode solution was measured:
[0068] Table 2
[0069]
[0070] In summary, the proton exchange membrane preparation method of this invention is simple, has high proton conductivity, and is much cheaper than commercial Nafion 117 membrane, so it has good application prospects. In actual experiments, the examples of this invention are used in fuel cells to remove iron ions from acid mine drainage (AMD) in the anode chamber. While generating electricity, the Fe ions in AMD can be removed. The maximum power density of Example 3 can reach 105mW / m 2 (like Figure 2 ), while the maximum power density of comparative example 1 is only 83mW / m 2Moreover, the removal rate of iron ions in the anode chamber AMD in Example 3 can reach 99%, which is higher than 93% in Comparative Example 1. The present invention is conducive to industrial promotion and has good industrial prospects.
[0071] It should be noted that the above embodiments can be freely combined as needed. The above description is only the preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention can have various changes and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a proton exchange membrane, characterized in that: The steps include: The sulfonated polyetheretherketone solution is prepared by dissolving the sulfonated polyetheretherketone in dimethyl sulfoxide, and the amino acid modified cellulose nanocrystal powder is added to obtain a uniform and stable solution, and the casting solution is obtained after filtering; the casting solution is used in an amount of 3-5 mL / cm 2 The casting liquid is dripped onto the membrane laying plate and maintained at 80° C. to 90° C. for 24 to 26 hours. The obtained composite membrane is the sulfonated polyetheretherketone / modified cellulose composite proton exchange membrane.
2. The method for preparing a proton exchange membrane according to claim 1, characterized in that: The sulfonated polyetheretherketone is prepared by the following steps: The polyetheretherketone particles are dried under vacuum conditions at 100°C to 120°C to remove moisture, and the dried polyetheretherketone particles are added to concentrated sulfuric acid at a mass volume ratio of 1g:10mL, and stirred at 25°C to 30°C for reaction for 3 to 5 hours, and then the temperature is raised to 50°C to 80°C within 30 to 50 minutes, and stirring is continued for 5-8 hours. The reaction product is slowly poured into deionized water containing ice cubes to obtain white filamentous sulfonated polyetheretherketone; the product is washed to neutrality; and dried to obtain yellow sulfonated polyetheretherketone with a sulfonation degree of 50 to 60%.
3. The method for preparing a proton exchange membrane according to claim 1, characterized in that: The cellulose nanocrystal powder is prepared by the following steps: adding microcrystalline cellulose to sulfuric acid with a mass fraction of 64% to 67% according to a mass volume ratio of 1g / 17.5mL to 1g / 20mL; stirring the suspension and heating it to 45℃ to 50℃ for 3.5 to 4.5 hours. After the reaction is completed, the solution is poured into water to terminate the reaction and obtain a CNC suspension; and the CNC is separated from the suspension by centrifugal washing.
4. The method for preparing a proton exchange membrane according to claim 3, characterized in that: The separation of CNC from the suspension by centrifugal washing specifically includes the following steps: the suspension is centrifuged at a speed of 11000-13000 rp / min for 30-45 minutes, and mixed after washing to obtain a mixed solution; the mixed solution is then placed in a dialysis bag with a molecular weight cutoff value of 8000-14000, and dialyzed until the pH value of the water reaches 6.5-7.0; the dialyzed sample is vacuum freeze-dried to obtain CNC powder.
5. The method for preparing a proton exchange membrane according to claim 1, characterized in that: Amino acid modified cellulose nanocrystalline powder is prepared by the following steps: CNC powder, NN dimethylformamide, L-serine, NN-diisocyanate carbodiimide, and 4-lutidine are added into a beaker at a molar ratio of 1 g: 10 mL: 6 mmol: 2.4 mmol: 1.8 mmol, shaken at room temperature, and then treated with 1-2% trifluoroacetic acid in anhydrous acetonitrile solution, DMF, 1-2% trifluoroacetic acid aqueous solution, anhydrous ethanol, an ethanol aqueous solution with a volume ratio of 1:3, and anhydrous ethanol, and finally vacuum dried to obtain amino acid modified CNC, named: CW-Fmoc-ser; the CW-Fmoc-ser obtained above is placed in a mixed solution to remove the protecting group, the mixed solution includes piperidine and NN dimethylformamide, and finally freeze-dried to obtain AAs modified CWs, named: CW-ser.
6. A proton exchange membrane, characterized in that: The proton exchange membrane is prepared by the preparation method described in any one of claims 1 to 5.
7. An application of a proton exchange membrane, characterized in that: The proton exchange membrane according to claim 6 is applied to a proton exchange fuel cell.
8. A proton exchange membrane fuel cell, characterized in that: The proton exchange membrane of the proton exchange membrane fuel cell is the proton exchange membrane described in claim 6.